DEKONSTRUKSI EPISTEMOLOGI USHUL FIKIH KLASIK DALAM WACANA HUKUM DIGITAL: TELAAH PEMIKIRAN NASR ABU ZAYD DAN KHALED ABOU EL FADL - Andika (Makkah: Journal Of Islamic Studies, 2025)
: This study examines the limitations of classical ushul fiqh epistemology in responding to legal challenges in the digital era. Traditional ushul fiqh, which is grounded in a textual-formalist and analogical logic approach, is considered inadequate in addressing the complexities of modern technology and society. In this context, two contemporary Muslim thinkers—Nasr Abu Zayd and Khaled Abou El Fadl—are analyzed as representatives of a new approach to Islamic law that emphasizes contextual and ethical interpretation. Nasr Abu Zayd highlights the importance of hermeneutics in interpreting religious texts, rejecting the notion of a singular, objective meaning and emphasizing the social and historical contexts of interpretation. Meanwhile, Khaled Abou El Fadl underscores the ethical and justice-oriented dimensions of ijtihad and Islamic legal production. Both thinkers offer a critique of authoritarian interpretation and propose a more inclusive, participatory, and relevant framework for engaging with contemporary digital legal issues such as AI-generated fatwas, crypto transactions, and personal data protection. Using a qualitative approach and textual analysis, this study concludes that a reconstruction of ushul fiqh epistemology is necessary— one that is based on a contextual-ethical perspective. These findings are crucial for developing an Islamic legal framework that is more responsive to digital realities and for opening methodological reform within contemporary Islamic studies.